Electrospun Biomaterials in the Treatment and Prevention of Scars in Skin Wound Healing - Mulholland, Eoghan J. (Frontiers in Bioengineering and Biotechnology, 2020)
Electrospinning is a promising method for the rapid and cost-effective production of nanofibres from a wide variety of polymers. The high surface area morphology of these nanofibres make for excellent wound dressings, and so have infinite potential in the prevention and treatment of scars. Wound healing and the resulting scar formation are exceptionally well characterised on a molecular and cellular level. Despite this, novel effective anti-scarring treatments which exploit this knowledge are still clinically absent. As the process of electrospinning can produce fibres from a variety of polymers, the treatment avenues for scars is vast, with therapeutic potential in choice of polymers; drug incorporation; and cell-seeded scaffolds. It’s essential to show the new advances in this field, thus, this review will investigate the molecular processes of wound healing and scar tissue formation, the process of electrospinning and examine how electrospun biomaterials can be utilised and adapted to wound repair in the hope of reducing scar tissue formation and conferring an enhanced tensile strength of the skin. Future directions of the research will explore potential novel electrospun treatments, such as gene therapies, as targets for enhanced tissue repair applications. With this class of biomaterial gaining such momentum and having such promise, it is essential to refine our understanding of its process to be able to combine this technology with cutting-edge therapies to relieve the burden scars have on world healthcare systems.